Verbalisme Bahasa Arab Dalam Kehidupan Beragama Masyarakat Muslim - Inchinia Angger Rowin (Nazhruna: Jurnal Pendidikan Islam, 2018)
Religious life and language have a very close relationship that affects the lives of the people. The role of language in religious studies is very important for its adherents, so that when they read religious texts or listen to their appeals they can make them understand the content and purpose of the text. For the Muslim community the Arabic language becomes a major that they must master and understand because the original sources of Islamic teachings and sciences are Arabic, so it is very important for Muslims especially their scientists to learn, understand, and master the Arabic language. Otherwise, it is difficult for us to study Islam from its original source derived from Arabic. However, this is the most special problem in Islamic societies. As a result of unwell understanding Arabic, unfortunately religion becomes easy to sell, religion is easily diverted, religion brought by unscrupulous person in deviation path, religion used as media for certain purposes. Arabic verbalism has happened in Muslim society in Indonesia, they make Arabic as formality, only just a form. So there is no inner or deep value inside of it. It is necessary to reform efforts in its wrong ideology, including changing the culture of verbalism in society, to put the position of Arabic language not only to memorize but used as a tool in deepening knowledge, one of the science of religion.